2019
DOI: 10.3390/cells9010084
|View full text |Cite
|
Sign up to set email alerts
|

A Septin Cytoskeleton-Targeting Small Molecule, Forchlorfenuron, Inhibits Epithelial Migration via Septin-Independent Perturbation of Cellular Signaling

Abstract: Septins are GTP-binding proteins that self-assemble into high-order cytoskeletal structures, filaments, and rings. The septin cytoskeleton has a number of cellular functions, including regulation of cytokinesis, cell migration, vesicle trafficking, and receptor signaling. A plant cytokinin, forchlorfenuron (FCF), interacts with septin subunits, resulting in the altered organization of the septin cytoskeleton. Although FCF has been extensively used to examine the roles of septins in various cellular processes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…The low toxicity level makes FCF a potential candidate for therapeutic applications of septin dependent disorders. However, off-target effects were reported before [ 40 , 41 ]. Modification of the chemical structure of FCF might lead to the development of new analogues with improved therapeutic potential and less side effects [ 42 , 43 ].…”
Section: Cell Biology Of Septinsmentioning
confidence: 98%
“…The low toxicity level makes FCF a potential candidate for therapeutic applications of septin dependent disorders. However, off-target effects were reported before [ 40 , 41 ]. Modification of the chemical structure of FCF might lead to the development of new analogues with improved therapeutic potential and less side effects [ 42 , 43 ].…”
Section: Cell Biology Of Septinsmentioning
confidence: 98%
“…The HT29 clone, HT29cl.f8, is derived from a single cell of HT29 and spontaneously polarizes under standard conditions in glucose and display important characteristics for permeability studies such as microvilli, tight junctions and a high TER [178]. This particular clone, can therefore be an alternative and have been used in several studies to model the intestinal barrier [179,180].…”
Section: Ht29 Cell Linementioning
confidence: 99%
“…Indeed, several studies have demonstrated that loss of SEPT7 destabilizes other subunits of the septin oligomers and triggers their degradation. 27,28 The septin rod oligomers spontaneously collide to form short filaments that can further assemble by end-to-end joining or lateral interactions into bundles, rings, gauzes, and sheer-like structures (Figure 1). 8,29 It is noteworthy that the composition of septin oligomers is primarily based on the in vitro reconstitution studies that utilized purified recombinant septin proteins.…”
Section: Assembly and Interactions Of Septin Proteinsmentioning
confidence: 99%
“…85 Downregulation of SEPT2 and SEPT7 expression increases permeability of model bronchial and intestinal epithelial cell monolayers, respectively. 28,85 In vascular endothelium, loss of SEPT2 accelerates leakiness of a resting endothelial barrier, 86 as well as exaggerates barrier disruption and attenuates barrier recovery following endothelial stimulation with thrombin. 87 Interestingly, increased vascular permeability of SEPT2-depleted endothelium promotes transendothelial migration of natural killer cells.…”
Section: Regulation Of Tissue Barriersmentioning
confidence: 99%
See 1 more Smart Citation